Existential approach to group psychotherapy - Kočiūnas, Rimantas (Psichologija, 2009)
The review discusses a model of working with psychotherapeutic groups, based on the existential psychotherapy paradigm developed by the author and called “existential experience group”. Its main concept is the idea of the human being as being-in-theworld (Dasein). The process of psychotherapy has two major directions, the first being an attempt to understand the problems of participants in the context of the main dimensions – physical, social, psychological and spiritual – of human life, and the second exploration of participants’ life difficulties in the context of “givens” (universal conditions) of existence. The following “givens” are described as essential: “thrownness” in the world, relations to others, the finiteness of life, freedom and responsibility, anxiety, meaning and meaninglessness, experience of time. The existential experience group represents a structured life situation in which participants with their unique life stories and experiences, involved in transactions among themselves and with the therapist, attempt to develop a common group life. The “group life” is a concentrated expression of individual lives of participants. The problems of participants are treated as certain inadequacies of current ways of “being-in-the-world”, as distortions of individual relation to existential “givens”. The group discusses the problems of participants not in relation to their personal life story (though it is given consideration as well), but rather in the context of the collectively created group life. The author discusses the universal objectives of the existential experience group, the main points of its functioning and ways of work. The basic structure of the group work is provided by the most usual norms of groups (openness and sincerity, interrelatedness of freedom and responsibility, sharing responsibility among participants and the therapist, confidentiality and regulated communication of participants outside the group) and also by changes of “developmental periods” of the group (“childhood”, “youth”, “maturity” and “old age”). The contents of sessions of existential experience groups is not planned in advance. It is determined by participants’ therapeutic goals and interpersonal situations arising “here and now”. Also, the position of the therapist in an existential experience group is analysed, since it is a greatly significant part of the psychotherapeutic work. The author stresses the importance of the therapist as phenomenologically oriented, giving priority to the participants’ experience as conceived by themselves. The main attitudes of the therapist are empathy and neutrality. For the therapist, it is critical to remain a real person in the group, a live human being with his own obligations and specific responsibility in the group. In an existential experience group, therapeutic changes are pursued by constantly directing participants to consciously reflect the conditions of humans’ being-in-the-world. Changes in understanding oneself and life are considered most essential.